2021
DOI: 10.2196/27341
|View full text |Cite
|
Sign up to set email alerts
|

Emotions of COVID-19: Content Analysis of Self-Reported Information Using Artificial Intelligence

Abstract: Background:The COVID-19 pandemic has disrupted human societies around the world. This public health emergency was followed by a significant loss of human life; the ensuing social restrictions led to loss of employment, lack of interactions, and burgeoning psychological distress. As physical distancing regulations were introduced to manage outbreaks, individuals, groups, and communities engaged extensively on social media to express their thoughts and emotions. This internet-mediated communication of self-repor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 88 publications
(88 reference statements)
0
21
0
Order By: Relevance
“…Indeed, a growing body of evidence indicates that people report a range of emotional responses linked to different aspects of climate change, such as sadness, grief, distress, despair, disgust, anger, fear, anxiety, helplessness and hopelessness but also hope or fascination [11][12][13][14][15][16][17] . Similarly, research has shown that people report various emotions regarding the COVID-19 pandemic, both positive (e.g., relaxation, happiness) and negative (e.g., stress, anxiety, depression), and that these emotions can co-occur 29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a growing body of evidence indicates that people report a range of emotional responses linked to different aspects of climate change, such as sadness, grief, distress, despair, disgust, anger, fear, anxiety, helplessness and hopelessness but also hope or fascination [11][12][13][14][15][16][17] . Similarly, research has shown that people report various emotions regarding the COVID-19 pandemic, both positive (e.g., relaxation, happiness) and negative (e.g., stress, anxiety, depression), and that these emotions can co-occur 29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Chen et al [17] used dimension reduction and cluster analysis to support comparison between viral COVID-19 posts in Twitter and Sina Weibo, a non-English-speaking platform in China. In some cases, multiple artificial intelligence approaches can be used to construct an observation framework, such as [18] where a combination of several machine learning approaches is proposed, including natural language processing, word embeddings and Markov models to investigate COVID-19 related emotions. Exploring vaccine hesitancy through online posts in social media is inspiring.…”
Section: Previous Work On Vaccines and Social Mediamentioning
confidence: 99%
“…In general, only tweets written in English were accepted, restricted to the US, with just a couple of exceptions. For example, in [ 20 ], the studied tweets were restricted to those that originated in Australia only, in contrast to the survey made by [ 23 ], which uses a global dataset. Each study implements its own filtering criteria, making comparing results difficult, especially since they have not made their data sets public.…”
Section: Introductionmentioning
confidence: 99%